Negotiating international civil society support: the case of Ethiopia's 2009 Charities and Societies Proclamation. Issue 5 (4th July 2019) - Birru, Jalale Getachew; Wolff, Jonas
ABSTRACT: Since 2005, international civil society support has faced increasing resistance around the world. Ethiopia is widely recognized as a key example of this so-called Closing Space phenomenon. With the 2009 Charities and Societies Proclamation (CSP) Ethiopia has established strict regulations on civil society organizations that, in particular, restrict the ability of local associations to make use of foreign funding and the range of activities allowed for foreign (funded) organizations. This paper traces the process of international negotiations that has accompanied the drafting of the CSP and identifies the consequences of these negotiations for international civil society support in the country. Focusing on the interaction between foreign "donors" and the Ethiopian government, it analyzes (a) what precisely these negotiations have been about, (b) to what extent these negotiations have actually influenced the content of the CSP, and (c) how the CSP as finally adopted has actually affected international civil society support in Ethiopia.